The Micro-food Web: Communities in Various Compositions of Composted Organic Matter - Maharning Ardhini R.; Ryandini Dini; Ardli Erwin R.; Khafida Wilda (E3S Web of Conferences)
The micro-food web decomposer is the primary community of the soil food web responsible for organic matter transformation in terrestrial ecosystems, providing minerals for plant growth. Their composition, however, depends on the quality of organic matter as their basal resource, which, in turn, determines the available nutrients in the soil. Our study examined the micro-food web community over three different organic matter compositions, differentiated by their organic carbon and total nitrogen contents. We compared the communities of composted organic matter that differed in their C to N proportion. Given in percent, they were 40:40:20, 50:40:10, and 60:30:10 of high C to N, medium C to N, and low C to N, respectively. After four weeks of finished composting, samples were obtained and enumerated for bacterial number, fungal biovolume, protozoan (amoebae, testate-amoebae, ciliate, flagellate), and nematode abundances. Our data show that a 20% change in low quality organic matter (high C to N ratio) suggests an 82.47% decline in bacterial abundance but a 22.15% increase in fungal abundance. These findings emphasize the importance of the organic matter Carbon and Nitrogen content in determining the composition of the micro-food web communities and the potential to manage the intended micro-food web community during the composting process for soil health improvement.